Phage-inspired targeting of antibiotic-loaded polymeric micelles for enhanced therapeutic efficacy against monomicrobial sepsis - Ozbek, Tulin; Demir, Hatice; Dokuz, Senanur; Tasdurmazli, Semra; Ozbey, Utku; Ozbil, Mehmet; Topuzogullari, Murat; Cinar, Irfan; Karamese, Murat; Karamese, Selina Aksak; Acar, Serap; Bayrak, Omer Faruk; et al. (ELSEVIER, 2025)
The rapid increase in bacterial resistance to existing treatments underscores the critical need for novel therapeutic strategies. Here, an innovative approach using targeted nanocarrier systems that mimic phage-bacteria interactions through phage receptor binding protein (Gp45 from the phi 11 lysogenic phage) or derived peptides (P1, P2, P3, P4, P5), are introduced. These nanodrugs, exhibited receptor-ligand specificity and strong binding affinity, for the first time, were employed for the precise delivery and targeting of antibiotics within living organisms. The actively targeted micelles via two methods were produced; conjugating GP45 to dual antibioticloaded PLGA-b-PEG micelles (MiGp45) and the synthesis of peptide-conjugated micelles with dual antibioticloaded PLGA-b-PEG-peptide triblock copolymers. The untargeted nano-drug reduced MIC values by 2-10 times for vancomycin and 9-75 times for oxacillin, resulting in a synergistic effect. MiGp45 and MiP1-targeted micelles further reduced MIC values at least twofold, up to ninefold in resistant strains, indicating significant antibacterial improvement. In a mouse model of sepsis by S. aureus, MiGp45 treatment resulted in complete recovery as opposed to death in the untreated group, significantly reduced bacterial load, pro-inflammatory cytokine expression, lung injury, and normalized oxidative stress. The phage-based nanodrugs show tremendous promise as a highly effective antimicrobial treatment targeting multidrug- resistant pathogens.
Keywords: Phage-based targeting; Dual antibiotic-loaded nanodrug; S. aureus infection; Pneumonia sepsis; DRUG; RELEASE; PLGA; PEG; Chemistry; Pharmacology & Pharmacy